Productivity and nutrients use efficiency for cultivar of coffee plant - Amaral, José Francisco Teixeira do; Martinez, Herminia Emilia Prieto; Laviola, Bruno Galveas; Tomaz, Marcelo Antonio; Fernandes Filho, Elpidio Inácio; Cruz, Cosme Damião (Coffee Science - ISSN 1984-3909, 2011)
The optimization of the nutritional efficiency is of great importance to enlarge the productivity, to reduce the production cost and to increase the income of the rural producer. They were appraised four varieties of arabic coffee (Acaiá IAC 474-19, Icatu Amarelo IAC 3282, Rubi MG 1192 and Catuaí Vermelho IAC 99) as for the productivity of grains, to the agronomic efficiency and of absorption of nutrients. For so much, an experiment was carried out in field conditions whose treatments were distributed in factorial arrangement (4 x 3) x 4, constituted of four varieties, three levels of the fertilization (lower, normal and high) and four repetitions, arranged in randomized blocks. The plants that constituted the normal level received fertilization based in the march of accumulation of nutrients in Arabic coffee. The variety Icatu Amarelo IAC 3282 was the most productive in conditions field with restriction of nutrients, while the varieties Rubi MG 1192 and Catuaí Vermelho IAC 99 were shown more productive with high supply of nutrients. With low doses of fertilizers and correctives (low level), the variety Icatu Amarelo IAC 3282 it tended to present the best agronomic efficiency as for all the studied nutrients, and Acaiá IAC 474-19 it tended to present the worst ones.